A Cost-Effectiveness Analysis of Clopidogrel for Patients with Non-ST-Segment Elevation Acute Coronary Syndrome in China. Issue 9 (September 2016) - Cui, Ming; Tu, Chen; Chen, Er; Wang, Xiao; Tan, Seng; Chen, Can
Abstract Introduction There are a number of economic evaluation studies of clopidogrel for patients with non-ST-segment elevation acute coronary syndrome (NSTEACS) published from the perspective of multiple countries in recent years. However, relevant research is quite limited in China. We aimed to estimate the long-term cost effectiveness for up to 1-year treatment with clopidogrel plus acetylsalicylic acid (ASA) versus ASA alone for NSTEACS from the public payer perspective in China. Methods This analysis used a Markov model to simulate a cohort of patients for quality-adjusted life years (QALYs) gained and incremental cost for lifetime horizon. Based on the primary event rates, adherence rate, and mortality derived from the CURE trial, hazard functions obtained from published literature were used to extrapolate the overall survival to lifetime horizon. Resource utilization, hospitalization, medication costs, and utility values were estimated from official reports, published literature, and analysis of the patient-level insurance data in China. To assess the impact of parameters' uncertainty on cost-effectiveness results, one-way sensitivity analyses were undertaken for key parameters, and probabilistic sensitivity analysis (PSA) was conducted using the Monte Carlo simulation. Results The therapy of clopidogrel plus ASA is a cost-effective option in comparison with ASA alone for the treatment of NSTEACS in China, leading to 0.0548 life years (LYs) and 0.0518 QALYs gained per patient. From the public payer perspective in China, clopidogrel plus ASA is associated with an incremental cost of 43, 340 China Yuan (CNY) per QALY gained and 41, 030 CNY per LY gained (discounting at 3.5% per year). PSA results demonstrated that 88% of simulations were lower than the cost-effectiveness threshold of 150, 721 CYN per QALY gained. Based on the one-way sensitivity analysis, results are most sensitive to price of clopidogrel, but remain well below this threshold. Conclusion This analysis suggests that treatment with clopidogrel plus ASA for up to 1 year for patients with NSTEACS is cost effective in the local context of China from a public payers' perspective. Funding Sanofi China.